2002
DOI: 10.1086/342289
|View full text |Cite
|
Sign up to set email alerts
|

Family-Based Analysis Using a Dense Single-Nucleotide Polymorphism–Based Map Defines Genetic Variation at PSORS1, the Major Psoriasis-Susceptibility Locus

Abstract: Psoriasis is a common skin disorder of multifactorial origin. Genomewide scans for disease susceptibility have repeatedly demonstrated the existence of a major locus, PSORS1 (psoriasis susceptibility 1), contained within the major histocompatibility complex (MHC), on chromosome 6p21. Subsequent refinement studies have highlighted linkage disequilibrium (LD) with psoriasis, along a 150-kb segment that includes at least three candidate genes (encoding human leukocyte antigen-C [HLA-C], alpha-helix-coiled-coil-ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
121
1
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(131 citation statements)
references
References 42 publications
7
121
1
2
Order By: Relevance
“…49 A study from our group looking at both SNPs and classical HLA alleles revealed that haplotypes harboring HLACw*0602 and HLACw*1203 were over-transmitted to affecteds, suggesting that a variant or combination of variants exclusive to these haplotypes were predisposing. 50 Interestingly, one of these variants leads to acquisition of an additional site for the transcription factor RUNX, within intron 7.…”
Section: Psors1mentioning
confidence: 99%
“…49 A study from our group looking at both SNPs and classical HLA alleles revealed that haplotypes harboring HLACw*0602 and HLACw*1203 were over-transmitted to affecteds, suggesting that a variant or combination of variants exclusive to these haplotypes were predisposing. 50 Interestingly, one of these variants leads to acquisition of an additional site for the transcription factor RUNX, within intron 7.…”
Section: Psors1mentioning
confidence: 99%
“…Some CDSN single nucleotide polymorphisms (SNPs) have been associated with psoriasis in many genetic studies (reviewed by Capon et al, 2002), and a recent study revealed that only two genes from PSORS1, HLAC and CDSN, yield protein alleles that are unique to risk haplotypes (Nair et al, 2006). However, according to the latter study and others, the exact identity of the PSORS1 gene remains controversial (Veal et al, 2002;Capon et al, 2003;Helms et al, 2005;Orrù et al, 2005;Nair et al, 2006). Intriguingly, the only monogenic disease identified so far to be associated with mutations in CDSN revealed a hair phenotype and did not affect the epidermis (Levy-Nissenbaum et al, 2003); hypotrichosis simplex of the scalp (HSS; OMIM 146520) is a rare autosomal-dominant disease characterized by progressive loss of scalp hair resulting in almost complete baldness by the third decade.…”
Section: Introductionmentioning
confidence: 99%
“…2 Genome-wide linkage scans have unambiguously mapped a primary disease susceptibility locus (PSORS1) to the major histocompatibility complex (MHC), 3 where refinement studies and resequencing efforts point to HLA-C as the most likely PSORS1 candidate. 4,5 More recently, the advent of genome-wide association scans has allowed the identification of several non-MHC susceptibility genes, including IL12B, IL23R, RNF114, TNFAIP3, TNIP1, IL4/IL13 and LCE3B/3C [6][7][8][9][10][11] Of these, IL12B and IL23R harbour variants that also confer susceptibility to Crohn's disease (CD) 12 and ankylosing spondylitis. 13 Similarly, TNFAIP3 alleles have been associated with rheumatoid arthritis, 14 systemic lupus erythematosus 15 and type I diabetes.…”
Section: Introductionmentioning
confidence: 99%